Architecture and key technology of public computing communication network - TONG Xiao-yu 1; ZHANG Yun-yong 1; DAI Yuan-shun2 (Tongxin xuebao)
The development processes of public communication network and computing were reviewed.Then a new concept of public computing communication network was proposed and analyzed in detail.The inevitable evolution of public communication network into PCCN was elaborated.The architecture,entities and key technologies of PCCN were discussed in detail.